2020
DOI: 10.1108/jadee-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of ICT investments in bakery and sugar confectionery processed food sub-sector in India

Abstract: PurposeInformation and communication technology (ICT) is a general-purpose technology, which plays an important role in improving the efficiency of a business firm. Nowadays, investment on ICT has become necessary for every business firm in different sectors of the economy. However, firms need to be very cautious while investing on a particular ICT, which is suitable for their businesses. Thus, it becomes necessary for the firm to understand its internal organizational characteristics to invest better on ICT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…They found that these applications helped in providing anticipative vision in farming activities, driving real-time operational decisions and redesigning business processes for exceptional business models. Navyashree and Bhat (2020) conducted a study on how AI can change the agricultural landscape and mentioned that latest technologies, such as drone-based image processing techniques and precision farming techniques, can make farming more efficient. Selvaraj et al.…”
Section: Literature Review On Agricultural Value Chain Actorsmentioning
confidence: 99%
“…They found that these applications helped in providing anticipative vision in farming activities, driving real-time operational decisions and redesigning business processes for exceptional business models. Navyashree and Bhat (2020) conducted a study on how AI can change the agricultural landscape and mentioned that latest technologies, such as drone-based image processing techniques and precision farming techniques, can make farming more efficient. Selvaraj et al.…”
Section: Literature Review On Agricultural Value Chain Actorsmentioning
confidence: 99%